Download as pdf or txt
Download as pdf or txt
You are on page 1of 8

Created by R.

Dlin

“Chapter ’n Verse” – Inverting Functions in Two-Dimensions


Summary

In math, and in fact in apparently non-mathematical situations, a function can be thought of as a machine (or a
process) that converts items fed into it into other items according to a consistent rule. For example, a freezer converts
water into ice, consistently – it never converts water into anything other than ice. However a freezer works on more
things than just water. It can convert strawberries to frozen strawberries, bread to frozen bread, etc. In the case of
the freezer, the consistent rule is that it will freeze anything you put into it.

Now suppose someone gives you a block of ice, and tells you that they just took it out of a freezer. Could you
determine what it was that went into the freezer based on knowing what it was when it came out? Of course
the logical answer is to say water. And for the most part, that would be correct. However there are some other
possibilities that are not as immediately obvious – it could have been snow when it went in, or it could already have
been a block of ice, placed in the freezer so that it would not melt. So if you are trying to say what went into the
freezer in order to produce the block of ice, you would have to say “assuming that no items which are already frozen
were placed in the freezer, then it must have been water that was placed there to create this block of ice”. Notice
also that if you wanted to convert the ice back into water you could use a process called “thawing”. In this example,
thawing ice would turn it into water, and freezing water would turn it back into ice. We say that “freezing” and
“thawing” are inverse operations. This makes sense, although we do have to stipulate that we are assuming that
whatever was frozen by our freezer was not already frozen when it went in – otherwise the thawing procedure would
turn it into something other than what it was before it went into our freezer.

In math when we talk about inverting functions, it is very analogous to the “freezing” vs. “thawing” scenario. We
might take a simple function, say a “one-adder”, which adds one to any number we give it. Thus if we knew that the
“one-adder” had produced a 7, we could very easily say that a 6 was used to create the 7. In other words, we could
create a new function, a “one-subtractor” that would undo whatever the “one-adder” had done. And we could turn
the process around as well. If we knew that the “one-subtractor” had produced a 9, we could use the “one-adder”
to determine that we had started with a 10.

Of course, describing this kind of thing using only English is cumbersome. So we can use function notation to simplify
the descriptions like so: If f (x) = x + 1 (the “one-adder”) and g(x) = x − 1 (the “one-subtractor”) then f and g are
inverses of eachother. We would write g(x) = f −1 (x) to indicate this. We could also write f (x) = g −1 (x) to describe
the exact same relationship. Note that the superscript “−1 ” is not an exponent in this case. It just means that the
function we are talking about is the inverse of some other function. So g −1 (x) is “g-inverse of x”, and f −1 (x) is
“f -inverse of x”.

Algebraically, given the definition of one function in terms of x, we can generally determine the definition of its
inverse by following 3 steps:

Steps for determining the inverse of a function

¬ Let y = f (x)
­ Solve for x
® Replace y with x in your result from Step 2 to get a new function whose input is the output from the original
function (i.e., the input x for the new function is the same as the output y from the old one).

1
Examples

1. Given f (x) = x + 7 we find f −1 (x) as follows:


Step ¬: Let y = f (x)
y =x+7
Step ­: Solve for x
y = x+7
y−7 = x
Step ®: Replace y with x to state the inverse

f −1 (x) = x − 7

2. Given f (x) = −5x we find f −1 (x) as follows:


Step ¬: Let y = f (x)
y = −5x
Step ­: Solve for x
y = −5x
y
= x
−5
y
− = x
5
Step ®: Replace y with x to state the inverse
x
f −1 (x) = −
5
3. Given f (x) = 3x − 1 we find f −1 (x) as follows:
Step ¬: Let y = f (x)
y = 3x − 1
Step ­: Solve for x
y = 3x − 1
y+1 = 3x
y+1
= x
3
Step ®: Replace y with x to state the inverse
x+1
f −1 (x) =
3
x+5
4. Given f (x) = we find f −1 (x) as follows:
7
Step ¬: Let y = f (x)
x+5
y=
7
Step ­: Solve for x
x+5
y =
7
7y = x+5
7y − 5 = x
Step ®: Replace y with x to state the inverse

f −1 (x) = 7x − 5

2
−4
5. Given f (x) = − 8 we find f −1 (x) as follows:
2x + 1
Step ¬: Let y = f (x)
−4
y= −8
2x + 1
Step ­: Solve for x
−4
y = −8
2x + 1
−4
y+8 =
2x + 1
(y + 8) (2x + 1) = −4
−4
2x + 1 =
y+8
−4
2x = −1
y+8
−4 y+8
2x = −
y+8 y+8
−4 − (y + 8)
2x =
y+8
−4 − y − 8
2x =
y+8
−12 − y 1
x = ×
y+8 2
−12 − y
x =
2y + 16
y + 12
x = −
2y + 16
Step ®: Replace y with x to state the inverse
x + 12
f −1 (x) = −
2x + 16
x−3
6. Given f (x) = + 7 we find f −1 (x) as follows:
5x − 2
Step ¬: Let y = f (x)
x−3
y= +7
5x − 2
Step ­: Solve for x
x−3
y = +7
5x − 2
x−3
y−7 =
5x − 2
(y − 7) (5x − 2) = x−3
5xy − 2y − 35x + 14 = x−3
−2y + 17 = x + 35x − 5xy
17 − 2y = 36x − 5xy
17 − 2y = x (36 − 5y)
17 − 2y
= x
36 − 5y
Step ®: Replace y with x to state the inverse
17 − 2x
f −1 (x) =
36 − 5x

3
Restricting the Domain to Ensure the Inverse is a Function

Sometimes we can not determine the inverse of a function without first restricting its domain. This is exactly like
the “’freezing” vs. “thawing” example, where we have to say “assuming nothing was placed in the freezer that was
already frozen, we can determine what was placed in the freezer by thawing it.” In this analogy, we are restricting
the domain of the “freezing” function to only allow items which are not already frozen. In mathematics, we often
see this necessity when there is an even exponent in the function.

For example, if f (x) = x2 has produced a 16, we can not be sure if the number that was used was +4 or −4, so
we can not properly invert the squaring process unless we make an assumption. In this case, we can state that
we are assuming only non-negative numbers are allowed as inputs, and then confidently say that if the result was
16 the input must have been +4. We could also state that we are assuming only negative numbers are allowed as
inputs, and then confidently say that if the result was 16 the input must have been −4. Note that this is the same
as restricting the domain of f (x) to x ≥ 0 or restricting it to x < 0 respectively. In these situations, we must state
the domain restriction we are assuming for f (x).

Examples

7. Given f (x) = x2 we find f −1 (x) as follows:


Step ¬: Let y = f (x)
y = x2
Step ­: Solve for x

y = x2

y = x

(x is now restriced to non-negative numbers, since we can not use ± y)

Step ®: Replace y with x to state the inverse



f −1 (x) = x

Domain restriction on f (x): D = {x|x ∈ R, x ≥ 0} ⇒ Range of f −1 (x): R = {y|y ∈ R, y ≥ 0}.


8. Sometimes, we must complete the square in order to isolate x:
Given f (x) = x2 − 6x + 7 we find f −1 (x) as follows:
Step ¬: Let y = f (x)
y = x2 − 6x + 7
Step ­: Solve for x

y = x2 − 6x + 7
y = x2 − 6x + 9 − 9 + 7
2
y = (x − 3) − 2
2
y+2 = (x − 3)
p
y+2 = x − 3 (Note this means that x ≥ 3 now)
p
3+ y+2 = x

Step ®: Replace y with x to state the inverse



f −1 (x) = 3 + x+2

Domain restriction on f (x): D = {x|x ∈ R, x ≥ 3} ⇒ Range of f −1 (x): R = {y|y ∈ R, y ≥ 3}.

4
9. Given f (x) = 4x2 − 48x + 117 we find f −1 (x) as follows:
Step ¬: Let y = f (x)
y = 4x2 − 48x + 117
Step ­: Solve for x

y = 4x2 − 48x + 117


4 x2 − 12x + 117

y =
4 x2 − 12x + 36 − 36 + 117

y =
= 4 x2 − 12x + 36 − 144 + 117

y
2
y = 4 (x − 6) − 27
y + 27 2
= (x − 6)
√ 4
y + 27
= x − 6 (Note this means that x ≥ 6 now)
√ 2
y + 27
6+ = x
2

Step ®: Replace y with x to state the inverse



x + 27
f −1 (x) = 6 +
2
Domain restriction on f (x): D = {x|x ∈ R, x ≥ 6} ⇒ Range of f −1 (x): R = {y|y ∈ R, y ≥ 6}.
10. Given f (x) = −3x2 + 12x + 5 we find f −1 (x) as follows:
Step ¬: Let y = f (x)
y = −3x2 + 12x + 5
Step ­: Solve for x

y = −3x2 + 12x + 5
= −3 x2 − 4x + 5

y
= −3 x2 − 4x + 4 − 4 + 5

y
= −3 x2 − 4x + 4 + 12 + 5

y
2
y = −3 (x − 2) + 17
2
y − 17 = −3 (x − 2)
r
y − 17
= x − 2 (Note this means that x ≥ 2 now)
−3
r
17 − y
2+ = x
3

Step ®: Replace y with x to state the inverse


r
−1 17 − y
f (x) = 2 +
3

Domain restriction on f (x): D = {x|x ∈ R, x ≥ 2} ⇒ Range of f −1 (x): R = {y|y ∈ R, y ≥ 2}.

5
11. Given f (x) = −5x2 + 3x + 9 we find f −1 (x) as follows:
Step ¬: Let y = f (x)
y = −5x2 + 3x + 9
Step ­: Solve for x

y = −5x2 + 3x + 9
 
3
y = −5 x2 + +9
5
 
2 3 9 9
y = −5 x + + − +9
5 100 100
 
3 9 9
y = −5 x2 + + − +9
5 100 20
 2
3 9 180
y = −5 x − − +
10 20 20
 2
3 171
y = −5 x − +
10 20
 2
171 3
y− = −5 x +
20 10
 2
20y 171 3
− = −5 x +
20 20 10
 2
20y − 171 3
= −5 x +
20 10
 2
20y − 171 3
= x+
−100 10
 2
171 − 20y 3
= x+
100 10
 2
171 − 20y 3
= x+
100 10
r  
171 − 20y 3 3
= x+ Note this means that x ≥ − now
100 10 10

171 − 20y 3
= x+
√ 10 10
3 171 − 20y
− + = x
10 √ 10
−3 + 171 − 20y
= x
10

Step ®: Replace y with x to state the inverse



−1 −3 + 171 − 20x
f (x) =
10
   
3 −1 3
Domain restriction on f (x): D = x|x ∈ R, x ≥ − ⇒ Range of f (x): R = y|y ∈ R, y ≥ − .
10 10

6
Exercises
Find the inverse for each of the following functions. Where necessary, state restrictions on the domain of f (x).

The exercises are grouped according to the examples that demonstrate how they can be solved.

1–8 In the style of examples 1–4


1. f (x) = x − 9 29. f (x) = 6x2
2. f (x) = 11x 30. f (x) = −3x2
3. f (x) = 5x + 1 31. f (x) = −5x2
4. f (x) = −2x + 3 32. f (x) = 2x2 − 5
5. f (x) = −4x − 7 33. f (x) = 4x2 − 1
x−1
6. f (x) = 5 34. f (x) = 8x2 + 7
x
7. f (x) = 2 +3 35. f (x) = −3x2 + 2
7x−3
8. f (x) = 5 36. f (x) = −9x2 + 4
9–23 In the style of examples 5–6 37. f (x) = −11x2 − 2
2
9. f (x) = x−9 38. f (x) = −x2 − 8
10. f (x) = 5
x+2
39. f (x) = x2 + 6x − 7

11. f (x) = −3 40. f (x) = x2 + 10x + 12


x−1

12. f (x) = 6 41. f (x) = x2 + 18x + 81


5x−3
2 42. f (x) = −x2 + 8x − 6
13. f (x) = 3x+1
4
43. f (x) = −x2 − 12x − 5
14. f (x) = 9x−7
44. f (x) = −x2 − 2x − 1
5
15. f (x) = 2x+3
45. f (x) = x2 + 7x + 2
−6
16. f (x) = 2x−5 46. f (x) = x2 + 5x − 6
−2
17. f (x) = 4x+1 47. f (x) = 3x2 + 12x − 1
−4
18. f (x) = 7x−8 48. f (x) = 5x2 − 80x + 77
−5
19. f (x) = 2x+5 49. f (x) = 7x2 − 14x − 3
20. f (x) = x+6
x−5
50. f (x) = −2x2 − 8x + 7

21. f (x) = x−2 51. f (x) = −9x2 + 36x + 2


4x+3

22. f (x) = 3x+4 52. f (x) = −4x2 − 40x − 19


x−8
2x−5 53. f (x) = 2x2 − 5x + 3
23. f (x) = 3x+7
54. f (x) = 7x2 + 3x + 2
24–60 In the style of examples 7–11
Remember to include a domain restriction for f (x). 55. f (x) = 21x2 − 17x + 39
24. f (x) = x2 56. f (x) = 11x2 − x − 1
25. f (x) = x2 − 6 57. f (x) = −3x2 − 2x + 4
26. f (x) = x2 + 7 58. f (x) = −5x2 + 5x + 6
27. f (x) = x2 + 3 59. f (x) = −13x2 − 11x + 91
28. f (x) = 2x2 60. f (x) = −7x2 − 2x − 12

7
Challenge Exercises
Find the inverse for each of the following functions. Where necessary, state restrictions on the domain of f (x).

These exercises are slightly different frome the examples but the steps to find the inverse are still the same.

1–5 Functions involving square roots.


1. f (x) = x

2. f (x) = x−3

3. f (x) = x+2+5

x−7+2
4. f (x) =
3

3x − 1 − 4
5. f (x) =
5

6–8 Functions involving square roots in the denominator.

1
6. f (x) = √
x
3
7. f (x) = √
x−3
5
8. f (x) = √ +5
x+2

9–15 Insanity.

9. f (x) = x3
10. f (x) = x4 − 10x2 + 25

11. f (x) = 3 x − 7

12. f (x) = 5 x2 + 1

3x − 7
13. f (x) = √
2x + 3
1
14. f (x) = √
4
x−9
s
2
15. f (x) = 3

x2 − 8x + 16

You might also like